Caregivers Lack of Disclosure Skills Delays Disclosure to Children with Perinatal HIV in Resource-Limited Communities: Multicenter Qualitative Data from South Africa and Botswana - Sphiwe Madiba (Nursing Research and Practice)
To promote the appropriate implementation of procedures for health disclosure to children, it is important to understand the reasons why caregivers delay the disclosure of healthcare information to children. This paper explored the views of caregivers on what makes disclosure to children with perinatal acquired HIV (PAH) difficult and what could make disclosure in these cases easier. Data were collected using focus group interviews with caregivers who were purposely selected from a multicenter study conducted in Botswana and South Africa. Forty-seven nondisclosed caregivers of children between 5 and 18 years who were receiving ART were interviewed. Caregivers felt that children should be told of their HIV-positive status despite the fact that none had disclosed this information to the children. The caregivers reported lack of disclosure skills but believed they were primarily responsible for disclosure to children and required support from healthcare workers (HCWs) during the disclosure process. They believed that counseling on how to approach disclosure and training on when and how to disclose will make the disclosure process easier. HCWs have a crucial role to play in promoting disclosure to perinatally infected children. The development of appropriate disclosure guidelines and training for HCWs will facilitate disclosure to children.